Economic Warfare and Supply Chain Management: Impacts and Solutions. - Mustapha Laafar; Ahmed Adri; Said Rifai (International Journal of Supply Chain Management, 2020)
In a sharp competition, the global SCM (Supply Chain Management) is based on the globalization of free trade following a liberal principle, which is appropriate to